2012
DOI: 10.1073/pnas.1200189109
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 fatty acids cause dramatic changes in TLR4 and purinergic eicosanoid signaling

Abstract: Dietary fish oil omega‐3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), elicit cardioprotective and anti‐inflammatory effects through unresolved mechanisms. EPA and DHA may reduce arachidonic acid (AA) metabolism and pro‐inflammatory effects by competition and inhibition at multiple levels. Here, we report the effects of AA, EPA, and DHA supplementation on membrane incorporation, phospholipase A2 release, and eicosanoid production in RAW264.7 macrophages. Each PUFA supplemented increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 40 publications
8
131
1
3
Order By: Relevance
“…This was found both in early work (20) and in recent lipidomic analyses (21)(22)(23)(24). Likewise, eosinophils (25)(26)(27) and mast cells (28)(29)(30)(31)(32) produce mainly LTC 4 , but apparently no or only small amounts of LTD 4 .…”
Section: Timeline Of Cell Culture and Coculturementioning
confidence: 57%
See 1 more Smart Citation
“…This was found both in early work (20) and in recent lipidomic analyses (21)(22)(23)(24). Likewise, eosinophils (25)(26)(27) and mast cells (28)(29)(30)(31)(32) produce mainly LTC 4 , but apparently no or only small amounts of LTD 4 .…”
Section: Timeline Of Cell Culture and Coculturementioning
confidence: 57%
“…Monocytic cells (macrophages, dendritic cells), mast cells, and eosinophils are fundamental previous studies on human blood monocytes and human peritoneal macrophages using incubation times up to 60 min [see (20) and references therein]. Also, in more recent lipidomic analyses of mouse peritoneal macrophages (21) and RAW264.7 murine macrophages (22,23), LTC 4 and 5-HETE (but not LTD 4 ) were major 5-LO products. In a recent study of macrophages, FACS-sorted from a mouse lung tumors, LTC 4 was more than 10-fold more abundant than LTD 4 (24).…”
Section: Formation Of Cyslt In Coincubations Of Pbecs With Mm6 Cellsmentioning
confidence: 99%
“…Weldon et al reported that DHA exhibits greater anti-inflammatory effect on human THP-1 macrophages as compared to that of EPA 25 . Norris and Dennis reported that EPA indirectly inhibits COX through elongation to n-3 DPA 26 . However, no information regarding the ability of n-3 DPA to regulate mRNA expression of pro-inflammatory factors in activated macrophages was described.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the expression and activation of eicosanoid-forming enzymes and their proximity to cPLA 2 , cells may preferentially shunt AA toward one of these pathways (6). Lipidomic analysis has been applied to study AA metabolism in mouse peritoneal Mfs (9), RAW264.7 Mfs (10,11), mouse mast cells (12), and Mfs from mouse lung tumors (13). Lipid mediators released from fully activated M1 and M2 human Mfs have also been determined (14).…”
mentioning
confidence: 99%